A clustering approach to identify and characterize the asthma and chronic obstructive pulmonary disease overlap phenotype. Issue 11 (1st August 2017) - Hirai, K.; Shirai, T.; Suzuki, M.; Akamatsu, T.; Suzuki, T.; Hayashi, I.; Yamamoto, A.; Akita, T.; Morita, S.; Asada, K.; Tsuji, D.; Inoue, K.; et al.
Summary: Background: Asthma and chronic obstructive pulmonary disease (COPD) are heterogeneous diseases. The phenotypes that have clinical features of both asthma and COPD are still incompletely understood. Objective: To clarify the best discriminators of the asthma‐COPD overlap phenotype from asthma and COPD subgroups using a clustering approach. Methods: This study assessed pathophysiological parameters, including mRNA expression levels of T helper cell‐related transcription factors, namely TBX21 (Th1), GATA3 (Th2), RORC (Th17) and FOXP3 (Treg), in peripheral blood mononuclear cells in asthma patients (n=152) and in COPD patients (n=50). Clusters were determined using k‐means clustering. Exacerbations of asthma and COPD were recorded during the 1‐year follow‐up period. Results: The cluster analysis revealed four biological clusters: cluster 1, predominantly patients with COPD; cluster 2, patients with an asthma‐COPD overlap phenotype; cluster 3, patients with non‐atopic and late‐onset asthma; and cluster 4, patients with early‐onset atopic asthma. Hazard ratios for exacerbation were 2.5 (95% confidence interval [CI], 1.1‐5.6) in cluster 1 and 2.3 (95% CI, 1.0‐5.0) in cluster 2 compared with patients in other clusters. Cluster 2 was discriminated from other clusters by total serum IgE level ≥310 IU/mL, blood eosinophil counts ≥280 cells/μL, a higher ratio of TBX21 / GATA3, FEV1 /FVC ratio <0.67 and smoking ≥10 pack‐years with an area under the curve of 0.94 (95% CI, 0.90‐0.98) in the receiver operating characteristic analysis. Conclusions and Clinical Relevance: The asthma‐COPD overlap phenotype was characterized by peripheral blood eosinophilia and higher levels of IgE despite the Th2‐low endotype.